Peran ZenCore dalam Meningkatkan Hasil Pembelajaran: Studi Kasus Pengguna Aplikasi Zenius - Indrasari, Gheasya Nonik; Baihaqi, Aufa Izzuddin (Universitas Gajah Putih, Indonesia, 2023)
Learning opportunities in the digital era are currently growing rapidly, as is the case with the education company PT Zona Edukasi Nusantara (Zenius) starting personalization by launching an online learning tutorial application under the name Zenius. Zenius currently has the rapidly growing Zencore feature, this feature will train the skills and knowledge of Zenius users. It is known that skills and knowledge are always mastered regardless of level of education, specialization, age or professional field. The research method used by the author is descriptive qualitative and data collection techniques are in the form of literature studies (including journal articles, books, and those related to the Zenius application) and interviews. The purpose of this research is to find out whether Zencore is able to improve the learning outcomes of Zenius application users.